Anopheles gambiae PGDB, AnoCyc, version 1.1 in Summary - M., Adebiyi; S., Fatumo; E., Adebiyi (Covenant Journal of Physical and Life Sciences, 2018)
Identification of novel insecticidal targets for the development of more effective insecticides is critical, discovery of new resistance mechanisms, computational analysis of biochemical pathways with various genomic data is essential for novel discoveries in proffering solution to the challenge of malaria vector eradication efforts world research community.Â Â  Dissection and comprehensive study of biochemical metabolic networks has great potential to effectively and specifically identify essential enzymes as potential insecticidal targets. Using the PathoLogic program, we have constructed AnoCyc, version 1.1, a pathway/genome database (PGDB) for A. gambiae AgamP3, using its annotated genomic sequence and other annotated information from Vector base, UNIPROT and KEGG databases. AnoCyc for AgamP3, the first PGDB for A gambiae has been deployed to BioCyc Database collection, which has a total size of about 273,093,681pb with 1237 compounds, 3684 Go terms, 255 pathways, 2380 enzymes without any protein complex, 1758 enzymatic reactions, 42 super pathways and several other components and their corresponding information.